An interlanguage study of request perspective: Evidence from German, Greek, Polish and Russian learners of English. - Eva Ogiermann; Spyridoula Bella (Contrastive Pragmatics, 2020)
This study examines request perspective, the least researched form of mitigation in requesting, while focusing on a type of request characterised by a strong preference for the speaker perspective in English and the hearer perspective in most other languages researched to date. It examines requests produced by 900 speakers from 9 different (inter)language groups: five groups of native speakers (English, German, Greek, Polish and Russian) and four groups of advanced learners of English as a foreign language (German, Greek, Polish and Russian L1s).  While the learners used more conventionally indirect forms than the native speakers of the respective L1s, thus showing awareness of this English pragmatic norm, they retained a preference for the hearer perspective. These results suggest a reliance on pragmatic universals as an alternative explanation to pragmatic transfer, also illustrating the need to address less salient pragmatic features in English language teaching.